The Sodium-Driven Chloride/Bicarbonate Exchanger in Presynaptic Terminals - Burette, Alain C. (2012)
The sodium-driven chloride/bicarbonate exchanger (NDCBE), a member of the SLC4 family of bicarbonate transporters, was recently found to modulate excitatory neurotransmission in hippocampus. By using light and electron microscopic immunohistochemistry, we demonstrate here that NDCBE is expressed throughout the adult rat brain, and selectively concentrates in presynaptic terminals, where it is closely associated with synaptic vesicles. NDCBE is in most glutamatergic axon terminals, and is also present in the terminals of parvalbumin-positive γ-aminobutyric acid (GABA)ergic cells. These findings suggest that NDCBE can regulate glutamatergic transmission throughout the brain, and point to a role for NDCBE as a possible regulator of GABAergic neurotransmission.